Dynamics of the BBM equation with a distribution force in low regularity spaces - Wang, Ming; Liu, Anping (Topological Methods in Nonlinear Analysis, 2018)
The Benjamin-Bona-Mahony equation with a distribution force on torus is studied in low regularity spaces. The global well-posedness and the existence of a global attractor in H^s,p(T) are proved.